2013
DOI: 10.1016/j.cemconcomp.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cement-based materials with nanoparticles

Abstract: a b s t r a c tThis is a summary paper on the work being done at the Center for Advanced Cement-Based Materials at Northwestern University on the modification of cement-based materials with nanoparticles, specifically nanoclays, calcium carbonate nanoparticles, and nanosilica. The rheological properties of clay-modified cement-based materials are investigated to understand the influence of nanoclays on thixotropy. The influence of the method of dispersion of calcium carbonate nanoparticles on rate of hydration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 458 publications
(193 citation statements)
references
References 21 publications
10
146
0
4
Order By: Relevance
“…This material is fine-grained and may cause deterioration of fluidity; however, this effect may be compensated by spherical grains of fly ash [87,88]. Accelerating action of small amount of silica fume on early hydration of high volume fly ash mixture may be manifested in changes of shape of heat release curve while improvement in pozzolanic activity by reduction in Ca(OH) 2 basing on TG/ DTG results.…”
Section: Silica and Aluminosilicate Pozzolanic Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…This material is fine-grained and may cause deterioration of fluidity; however, this effect may be compensated by spherical grains of fly ash [87,88]. Accelerating action of small amount of silica fume on early hydration of high volume fly ash mixture may be manifested in changes of shape of heat release curve while improvement in pozzolanic activity by reduction in Ca(OH) 2 basing on TG/ DTG results.…”
Section: Silica and Aluminosilicate Pozzolanic Materialsmentioning
confidence: 99%
“…Very fine grains of nanosilica act as nucleation centres for precipitating products; thus, hydration of cement is accelerated [87,89]. Interfacial transition zone is improved and compressive strength of final material is enhanced as a result of action of this additive despite its small amount used [87,92,95]. However, it should be indicated that very fine particles of nanosilica tend to agglomerate.…”
Section: Silica and Aluminosilicate Pozzolanic Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the isolated insertion of NTCP-OX as the nanocomposite T2 (insertion of 0.2% of NTCPM-OX) presented tensile strength 13% higher than the control material, which can be explained by the fact that materials such as NTC exhibit high tensile strength and when well distributed in the matrix results in a nanoscale reinforcement [19,20], according to figure 9, preventing the appearance of the first cracks, which results in the increase of tensile strength. …”
Section: Fig8: Tensile Strength By Flexural Stressmentioning
confidence: 97%